Analiza Persepolis Marjane Satrapi jako nietypowej kroniki ze względu na formę powieści graficznej (Jednostka wobec globalnego wymiaru stosunków międzynarodowych, 2021)
In this article, instead of referring directly to the problem of the individual as a subject in international relations, I will focus on finding a way to write about it. I’m interested in how to define a convenient narrative. Whether to focus on the individual perspective of the individual, or maybe try to take one side of the relationship or rather include a bilateral perspective. I assume that properly codified content must be accompanied by a new form. In search of unusual texts with given determinants, I intend to analyze the graphic novel Persepolis Marjane Satrapi. I will also use the neo-formal method of textual analysis, which I learned at cultural studies and historical method, thus combining two disciplines of the humanities. In the thought that art can be a universal language and creative expression a means of communication.